The Effect of Brexit on the UK Economy (so far) - Sindri Engilbertsson; Gylfi Zoega (Birkbeck, University of London, Birkbeck Centre for Applied Macroeconomics (BCAM), 2019)
The political turmoil in the UK following the referendum on future membership of the European Union in 2016 provides a natural experiment for studying the effects of political uncertainty (in the Knightian sense) on the economy. We find that the subsequent confusion and infighting in British politics has not affected the real economy much – employment is at a historical high and output growth is positive – but there are some signs of slowing investment and house price increases. The stock market has also not been much affected although it did fall after the referendum of 2016. The main effect of the Brexit vote and the subsequent political developments is found in the currency market where news that make a hard Brexit more likely cause the currency to depreciate. We conclude that leaving the European Union without an agreement is likely to make the currency depreciate and the stock market fall while output declines. In contrast, leaving with an agreement that gives continued access to the Single Market would likely make the currency appreciate, the stock market rise and employment and output increase further
Keywords: E24; E44; F31; 330; Brexit; growth; share price; currency market